2000
DOI: 10.1067/mva.2000.109204
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a venous anastomosis Tyrell vein collar on the primary patency of arteriovenous grafts in patients undergoing hemodialysis

Abstract: A Tyrell vein collar at the venous anastomosis of a forearm AVG resulted in premature graft failure. The use of a Tyrell vein collar may accelerate venous anastomosis intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 17 publications
(22 reference statements)
2
25
0
Order By: Relevance
“…98 Although these patches showed improved patency in arterial bypass grafts, according to Lemson et al, 47 the opposite was true for grafts used as vascular access for hemodialysis. 48 Gagne et al 20 perceived a similar phenomenon in their study where they put in a Tyrell vein collar at the venous anastomosis of a vascular access graft. The vein pieces to construct the collar are superficial forearm veins or saphenous vein branches.…”
Section: Compliance Mismatchmentioning
confidence: 86%
“…98 Although these patches showed improved patency in arterial bypass grafts, according to Lemson et al, 47 the opposite was true for grafts used as vascular access for hemodialysis. 48 Gagne et al 20 perceived a similar phenomenon in their study where they put in a Tyrell vein collar at the venous anastomosis of a vascular access graft. The vein pieces to construct the collar are superficial forearm veins or saphenous vein branches.…”
Section: Compliance Mismatchmentioning
confidence: 86%
“…However, trials of Tyrrell collar venous anastomosis in arteriovenous grafts (AVGs) not only showed no improvements in graft patency [155], but also indicated that the use of the collar at the venous anastomosis of forearm loop AVGs resulted in early graft failure [156]. …”
Section: Theories On Bypass Graft Failurementioning
confidence: 99%
“…9 The clinical application of the Venaflo grafts showed some improvements of the long term patency, however, there are still a number of cases in which significant venous stenosis has developed, and the overall results remain unfavorable. 10,11,13 The main drawback of a funnel-shaped anastomotic geometry is that in anastomotic expansions, separation areas develop invariably. This is a well known fluid mechanical principle of pipe flows where a sudden expansion of more than 6°to 7°is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…9 After the clinical introduction of the Venaflo grafts, however, the long-term patency of cuffed arteriovenous PTFE grafts remained poor. [10][11][12][13] This presumably is because the Venaflo graft has a wide cuffed outflow section that effectively reduces the shear forces, but as a result of the sudden anastomotic expansion, simultaneously promotes the creation of flow separation areas near the PTFE wall. In pipe flow, a flow separation invariably occurs when the mainstream-to-wall angle suddenly extends to more than 6°to 8°.…”
mentioning
confidence: 98%